2021
DOI: 10.1016/j.addma.2020.101630
|View full text |Cite
|
Sign up to set email alerts
|

Role of powder particle size on laser powder bed fusion processability of AlSi10mg alloy

Abstract: Laser powder bed fusion (L-PBF) is one of the most promising additive manufacturing (AM) methods which provides an exceptional opportunity to improve the existing designs and move toward fabricating fine features and complex geometries with higher efficiencies. Considering the layer-wise nature of this technique, the possibility of fabricating fine features is tied to the ability to deposit thin powder layers in this process. Since the powder layer thickness is directly dictated by the powder particle size, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 69 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…As the circularity and the Hausner ratio seemed to impact only the part density for WA powder, the influence of PLD on part density is evaluated in this section as the relevance of a high PLD for part quality is frequently stressed in literature [5,32,41,42]. Figure 12 shows the mean part porosity plotted against the PLD at scan speeds of 1000, 1500, and 2000 mm/s.…”
Section: Dependence Of the Part Density On The Powder Layer Densitymentioning
confidence: 99%
“…As the circularity and the Hausner ratio seemed to impact only the part density for WA powder, the influence of PLD on part density is evaluated in this section as the relevance of a high PLD for part quality is frequently stressed in literature [5,32,41,42]. Figure 12 shows the mean part porosity plotted against the PLD at scan speeds of 1000, 1500, and 2000 mm/s.…”
Section: Dependence Of the Part Density On The Powder Layer Densitymentioning
confidence: 99%
“…Spherical powder particles are in general superior to irregular shaped particles with respect to flowability and are consequently preferable. Also very small particle fractions (<10 µm) should be avoided as they might impair recoatability and bear difficulties with respect to occupational safety [ 40 ]. Based on these criteria W-, Mo-, and Ta-powder was purchased from Tekna Plasma Europe SAS (Mâcon, France).…”
Section: Methodsmentioning
confidence: 99%
“…However, Artzt et al (2020) found the converse. Similarly, as particle powder size reduces, enabling the creation of finer features in parts, Balbaa et al (2021) found that the surface roughness increases, whereas Conlon and Azari (2018) found the opposite. Oter et al (2020) found through varying part positioning within an EOS machine, that the roughness is dependent on the part geometry and inclination of the walls due to the machine's laser incidence.…”
Section: Build Parameter Studiesmentioning
confidence: 98%